Promoting public skin health through a national continuing medical education project on cosmetic and dermatologic sciences: a 15-year experience - Li, Yiming; Shu, Xiaohong; Huo, Wei; Wang, Xi (Frontiers in Public Health, 2023)
The developments in cosmetic sciences and technologies have generated a gap between the cosmetics and their users. Users including regular customers, clinicians, industry personnel, researchers, testing agencies, beauty salon workers, and mass media hardly possess the ability to distinguish truth from falsehood. The gap remained as one major reason for inappropriate cosmetics usage, insufficient efficacy, and even cosmetics adverse reactions (CARs).Methods: Aiming at enhancing the relevant practitioners' cosmetic and dermatologic sciences, we launched a cosmetic and dermatologic sciences continuing medical education (CME) since 2008. The objective of the current study was to evaluate the effectiveness of the CME. We summarized and analyzed the project for the last 15 years.Meanwhile, an online survey consisted of three parts was performed to evaluate the CME and to collect the trainees' comments.: A total of 3,923 trainees have participated in the CME project from 2008 to 2022. The trainees included clinicians, industry staffs, biomedical researchers, third-party cosmetics testing staffs, beauty salon staffs, students, and media staffs. The trainees had theory courses on cosmetic and dermatologic sciences, cosmetics DIY practice & video watching, and an optional guided tour during the 4.5-day CME. Eight hundred and twenty-three trainees and 586 control subjects responded to the online survey. The comprehensive test in the second part of the survey demonstrated that compared with the control group, the CME project significantly enhanced the trainees' perception and knowledge regarding the cosmetics formula sciences, basic dermatologic sciences, cosmetics usage, noninvasive measurements, new advances, CARs, and laws (P=0.000).Trainees of all occupations ranked "basic dermatologic sciences and skin diseases" as the most significant sections. Trainees of all occupations believed the CME has contributed most in "understand the function & efficacy of cosmetics". We noticed the occupational variances. Over 97% of trainees were willing to recommend the CME to the others.The CME project significantly enhanced the trainees' cosmetic and dermatologic sciences, which bridged the gap between cosmetics and public skin health. This multidisciplinary CME also contributed to establishing an interdisciplinary interaction and cooperation platform for the multiple occupations involved in the public skin health maintenance and promotion.